Molecular mechanisms governing exosome biogenesis, engineering strategies, and emerging role as cell-free therapeutics - Muhammad Hassan Raza; Javaria Ilyas; Kashf Shahid; Zania Urooj; Maria Tayyab Baig; Muhammad Shahid (Molecular Biology Reports, 2026)

Dual Inhibition of PTP1B and DPP-IV by Metabolites from Artocarpus elasticus Leaves Enhances Insulin Signaling and Sensitivity - Abdul Bari Shah; Muhammad Tayyab Khan; Safeer Ullah; Aizhamal Baiseitova; Muhammad Idrees; Il-Keun Kong; Ki Hun Park (Journal of Pharmaceutical Innovation, 2026)

Evaluation of the Air Pollution Mitigation Potential of Some Roadside Plants for Urban Forest Management - Mahrukh; Sohaib Muhammad; Muhammad Tayyab; Ali Ahmad; Zaher Uddin Babar; Nahaa M. Alotaibi; Muhammad Bilal; Amr Elkelish; Iqra Parvaz; Bushra Munam; Summiya Faisal; Muhammad Hasnain (Water, Air, & Soil Pollution, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

External energy-assisted surface modification of polymeric membranes for advanced separation applications: Mechanisms, performance, and scalability - Muhammad Tayyab Khalid; Mohammad Aadil; Chul Ho Park (Journal of Environmental Chemical Engineering, 2026)

SrTiO3 perovskite-controlled oxidation states of NiIn bimetallic sites for selectivity switch in CO2 hydrogenation - Muhammad Tayyab; Jung-Hyeok Park; Hyukjun Byun; Seongmin Jin; Byoungchul Son; Beomgyun Jeong; Chang-Ha Lee (Chemical Engineering Journal, 2026)

Proteome conserved multi-epitope-based vaccine construct against Nipah virus - Taimoor Khan; Tayyab Ali; Muhammad Suhaib Qudus; Gadallah Mohamed; Farukh S. Sharopov; Adam Junka; Yanfang Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Spectral decomposition-based inverted dynamical simulations of upper-Cretaceous petroleum-bearing energy resources, NE-Indus Onshore - Muhammad Tayyab Naseer; Ahmed J.R. Al-Heety; Muna Elsadig; D. Baba Basha; George Kontakiotis; Assimina Antonarakou; Abaker A. Hassaballa; Ilyas Khan; Hezam Al-Awah (Journal of Applied Geophysics, 2026)

Geospatial Assessment of Freshwater Quality for Heavy Metals and its Potential Health Risks Using Geoinformatics and Water Index Models in Gilgit-Baltistan-Pakistan - Naila Jabeen; Lubna Ghazal; Humaira Kanwal; Tayyab Raza Fraz; Muhammad Farrakh Nawaz; Liaquat Karim; Faten Khalid Karim; Samih M. Mostafa; Altaf Hussain Lahori (International Journal of Environmental Research, 2026)
Access to safe drinking water is a growing global challenge, with billions of people exposed to water scarcity and contamination risks. Heavy metals in drinking water are of particular concern due to their toxic effects on human health and ecosystems. This study assessed the drinking water quality of Hunza Valley, Gilgit-Baltistan, Pakistan, where no comprehensive geospatial evaluation had previously been conducted. A total of 66 water samples from springs and glaciers were analyzed for physico-chemical parameters and heavy metals (Fe, Ni, Cd, Cr-VI, As, and Pb). Statistical analysis (correlation, principal component analysis and cluster analysis), water quality indices (Water Quality Index and Synthetic Pollution Index), human health risk assessment (Hazard Quotient and Hazard Index) and geostatistical interpolation (Ordinary Kriging) were employed. Results showed that As (77%), Pb (34%), Cd (25%), and Cr-VI (9%) exceeded WHO limits, while Fe and Ni remained within permissible levels. WQI classified 59% of samples as unfit for human consumption, while SPI designated 26% as unsafe. PCA extracted four significant factors explaining 67% of total variance, and hotspot mapping highlighted Aliabad, Dorkhun, and Ganish as most contaminated villages. The hazard quotient and hazard index for non-carcinogenic health risk showed very few samples with significant health risk. The geospatial maps of health risk showed higher geospatial variability for arsenic, lead and iron whereas low variations were observed for cadmium, chromium and nickel. The TCRI values revealed As, Cd, Cr, Pb and Ni pose significant carcinogenic health risk with geospatial variation highlighting the western side of the district. The findings emphasize the urgent need for feasibility studies for treatment facilities, regular monitoring, cancer specific health risk studies to protect public health in Hunza Valley. This research provides a framework for sustainable water management aligned with SDG-6.

A novel multi-epitope mRNA vaccine against Escherichia coli using an in silico reverse vaccinology approach - Shakeela Parveen; Javeria Abbasi; Muhammad Hussain; Muhammad Farhan Khan; Muhammad Tayyab; Amina Parveen; Laiba Shafique (Journal of Applied Genetics, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

3D point cloud based optical tracking of dynamic quality degradation during drying of fruits and vegetables - Muhammad Tayyab; Barbara Sturm; Farhad Khoshnam; Mulugeta Admasu Delele; Arman Arefi (Journal of Food Engineering, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Stem Cells and their Key Derivatives in Degenerative Musculoskeletal Diseases - Nawaz Khan; Zeynab Ahmadova; Bin Zeng; Waqas Ahmed; Tayyab Shafiq; Zihao Zhang; Aiyuan Su; Nazim Muhammad; Sajid Khan; Yujie Liang; Li Duan (Stem Cell Reviews and Reports, 2026)

Surveillance of citrus canker: a threat to Pakistani citrus industry-status and distribution of citrus canker in major citrus growing regions of Pakistan - Safi Ullah; Zia ur Rehman; Muhammad Tayyab; Aamir Iqbal; Abdullah Jalal; Jinbiao Ma; Muhammad Awais; Sajid Ali (Journal of Plant Pathology, 2026)

Molecular characterization and gene expression of the HSP90 gene family in Cyprinus carpio and Oreochromis niloticus under thermal stress - Shakeela Parveen; Mehwish Sultana; Muhammad Tayyab; Muhammad Farhan Khan; Muhammad Hussain; Amina Parveen; Youhou Xu; Peng Zhu; Laiba Shafique (Fish Physiology and Biochemistry, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Regulation of biochemical attributes, photosynthetic pigments, and antioxidant activity in Zea mays L. for complete amelioration of heavy metal toxicity using synergistic application of arsenic-tolerant PGPR and nanoparticles - Mohsin Zafar; Humaira Yasmin; Tayyab Shafiq; Rabia Naz; Asia Nosheen; Muhammad Nadeem Hassan (Environmental Science and Pollution Research, 2026)

Timing of India-Asia diachronous collision: A view from the westernmost Indian margin, Pakistan - Muhammad Qasim; Owais Tayyab; Lin Ding; Javed Iqbal Tanoli; Muhammad Awais; Kamran Tabassum; Fulong Cai; Zhang Dingding; Ishtiaq A.K. Jadoon (Tectonophysics, 2026)

Convergence of Digital Twins and food drying technology: How to bring the next generation of dryers to life!? - Arman Arefi; Carlos Vilas; Mulugeta Admasu Delele; Petra Foerst; Sebastian Gruber; Mohammad Kaveh; Farhad Khoshnam; Norhashila Hashim; Maimunah Mohd Ali; Saman Zohrabi; Muhammad Tayyab; Aditya Parmar; et al. (Journal of Food Engineering, 2026)

Mechanistic insights into the synergistic pharmacology of quercetin–kaempferol against SARS-CoV-2 infection - Farman Ali; Muhammad Zubair Saleem; Muhammad Mohsin; Saleem Ahmad; Waqar Islam; Wasim Qasim; Muhammad Tayyab (In Silico Pharmacology, 2026)

Hyperspectral and 3D point cloud imaging unraveling of physio-chemical shifts during drying of purple carrot and golden kiwifruit - Muhammad Tayyab; Barbara Sturm; Mulugeta Admasu Delele; Arman Arefi (Food Control, 2026)

Integrating energy efficiency, economic growth, and regulatory compliance for China's clean energy transition: A route to net-zero emissions - Abdul Ghaffar; Muhammad Tayyab; Muhammad Umaiir (Next Research, 2025)

Genomic and molecular characterization of TGF-beta superfamily in Parus major - Mehwish Sultana; Shakeela Parveen; Muhammad Farhan Khan; Muhammad Tayyab; Muhammad Hussain; Saman Shabir; Warda Safdar; Laiba Shafique (Organisms Diversity & Evolution, 2025)

Spectral Quantitative Gas Saturation and Porosity-Constrained Lateral Variability Dynamical Simulations of Cretaceous Shale Gas-Bearing Deep-Water Reservoirs, NNE-Indus Onshore - Muhammad Tayyab Naseer (Natural Resources Research, 2025)

Organic Amendments Enhance Growth and Antioxidative Responses of Wheat (Triticum aestivum L.) Under Water Stress Conditions - Muhammad Tayyab Mehmood; Muhammad Anwar-ul-Haq; Muhammad Zia-ur-Rehman; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Tectonically-subsidized shallow-marine Cretaceous gas-bearing stratigraphic traps, shelf-slope basin, NW-Arabian Sea: Seismic attributes and broadband porosity-constrained seismic acoustic impedance variability dynamical reservoir simulations - Muhammad Tayyab Naseer (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Environmental pollution and green intergovernmental fiscal relations: Fiscal decentralization for sustainable governance - Fayaz Hussain Tunio; Zhao Rui Feng; Tayyab Raza Fraz; Muhammad Shahbaz; Naveed R. Khan; Shoh-Jakhon Khamdamov (Journal of Environmental Management, 2025)

Legacy Polyfluoroalkyl Substances (PFAS) Contamination in Ravi and Sutlej Rivers, Punjab, Pakistan: Assessing Ecological and Human Health Risks - Naveed Akhtar; Asia Iqbal; Arshad Javid; Muhammad Tayyab (International Journal of Environmental Research, 2025)

Seismic attributes and spectral waveform-constrained porosity-controlled dynamical simulations of lower-Cretaceous shale gas-bearing Lowstands prograding wedges and deep-water submarine fans, NE-Indus rifting delta - Muhammad Tayyab Naseer (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Spectral decomposition’ application images early-Cretaceous tectonically-controlled shallow-marine unconventional shale gas-bearing resources, SW-Asian Indus rift basin: Inverted velocity and density structural simulations - Muhammad Tayyab Naseer (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bioenergy by-products enhance the soybean photosynthesis, antioxidant defense, and related gene expression by modulating metal bioavailability in acidic soil - Muhammad Tayyab Sattar; Laiba Qazi; Sumaira Manzoor; Imran Khan; Wenjie Li; Hongju Ma; Fei Shen (Applied Soil Ecology, 2025)

Spectral decomposition-based static reservoir simulations of gas-bearing cretaceous deep-water resources, SE-Indus delta - Muhammad Tayyab Naseer (Journal of Applied Geophysics, 2025)

Fucosylation of hemocyanin is critical for antibacterial immunity in Penaeus vannamei - Mingming Jiang; Yiqi Liu; Jude Juventus Aweya; Shuaiqi Liang; Junyang Zhou; Muhammad Tayyab; Yongzhen Zhao; Qingyun Liu; Yueling Zhang; Zhihong Zheng (Fish & Shellfish Immunology, 2025)

How do digital government, circular economy, and environmental regulatory stringency affect renewable energy production? - Ilhan Ozturk; Sana Ullah; Sidra Sohail; Muhammad Tayyab Sohail (Energy Policy, 2025)

The Indonesian Throughflow regulated Australian summer monsoon across the Mid-Brunhes Event - Muhammad Sarim; Jian Xu; Xin Cheng; Peng Zhang; Junwen Wang; Maqsood Ur Rahman; Tayyab Jan; Hammad Ahmad (Quaternary Science Reviews, 2025)

Data-driven multi-hazard susceptibility and community perceptions assessment using a mixed-methods approach - Muhammad Hussain; Kashif Ullah; Muhammad Tayyab; Safi Ullah; Ashfaq Ahmad Shah; Jiquan Zhang; Zhijun Tong; Xingpeng Liu; Zahid Ur Rahman (Journal of Environmental Management, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Revolutionizing electrochemical sensing: Ultra-sensitive non-enzymatic detection of 4-aminophenol with a novel Cu-PANI nanocomposite - Muhammad Tayyab; Abdur Rahim; Muhammad Tariq; Zia Ul Haq Khan; Sana Sabahat; Jibran Iqbal; Dalia Fouad; Abdul Qadeer; Farid S. Ataya; Lubna Sherin (Journal of Water Process Engineering, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

Tectonostratigraphic framework of early-Cretaceous hydrocarbon-bearing deep-water architectures, divergent plate margins, NE-Arabian Sea: Spectral decomposition-based density-thickness-constraint lateral variability static reservoir simulations - Muhammad Tayyab Naseer (Gondwana Research, 2025)

The stability and in vitro digestion of resveratrol-loaded emulsion stabilized with peanut protein hydrolysate and dextran conjugate - Meiyue Wang; Guanhao Bu; Songye Shi; Ying Xin; Tingwei Zhu; Chenxian Yang; Xiaojie Duan; Muhammad Tayyab Rashid (Food Research International, 2025)

Regulating electron-hole pairs of g-C3N4 efficiently separated and fully utilized for photosynthesis of H2O2 under visible light - Zongwen Zhang; Chunyuan Chen; Muhammad Tayyab; Zhen Wei; Xiuzhen Zheng; Wenchao Shangguan; Sujuan Zhang; Shifu Chen; Sugang Meng (Chemical Engineering Journal, 2025)

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

From research to roadmaps: Electric vehicle studies driving sustainable policy frameworks - Hira Tahir; Sami El-Ferik; Muhammad Tayyab (Transportation Research Part D: Transport and Environment, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

A ternary dumbbell MoS2 tipped Zn0.1Cd0.9S nanorods visible light driven photocatalyst for simultaneous hydrogen production with organics degradation in wastewater - Muhammad Tayyab; Yaoshu Xie; Xianjun Tan; Muhammad Usman; Man-Chung Tang; Season Si Chen (Chemical Engineering Journal, 2025)

Retraction Note: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2025)

Quantitative appraisal of tectonically-influenced hydrocarbon-bearing Late-Cretaceous fluvial depositional system, Southwest Pakistan using spectral waveform-based instantaneous lateral thickness variability static simulations - Muhammad Tayyab Naseer (Journal of Asian Earth Sciences, 2025)

Cell Death in Crustacean Immune Defense - Zeyan Chen; Muhammad Tayyab; Defu Yao; Jude Juventus Aweya; Zhihong Zheng; Xianliang Zhao; Zhongyang Lin; Yueling Zhang (Reviews in Aquaculture, 2025)
Cell death mechanisms in crustaceans are a complex interplay of processes essential for maintaining cellular homeostasis and immune defense. Modes of cell death like apoptosis, necroptosis, and necrosis are well‐documented in crustaceans, serving crucial roles in removing damaged or infected cells. Unlike in other organisms, crustaceans likely lack pyroptosis, a type of programmed cell death associated with innate immunity and inflammation, because they do not possess the gasdermin genes essential for this process. Recently, NETosis and ferroptosis have emerged as significant mechanisms in pathogen defense. NETosis, involving the release of DNA fibers and antimicrobial proteins, helps trap and neutralize pathogens, while ferroptosis, an iron‐dependent form of cell death, contributes to lipid peroxidation and immune responses. Cuproptosis, although not yet studied in the context of crustacean immunity, shows potential crosstalk with ferroptosis, particularly in the regulation of metal ion homeostasis, oxidative stress, and cellular metabolism. Understanding these mechanisms offers promising applications in aquaculture, such as developing targeted immune modulators and enhancing disease resistance in economically important crustacean species.

Copper Homeostasis and Its Impact on Innate Immunity in Crustaceans - Hejia Chen; Xi Huang; Muhammad Tayyab; Mingming Zhao; Defu Yao; Zhihong Zheng; Xianliang Zhao; Yongzhen Zhao; Xiuli Chen; Bobo Zhang; Qiongqiong Yang; Yueling Zhang; et al. (Reviews in Aquaculture, 2025)
Copper, an essential micronutrient in crustaceans, plays vital roles in enzymatic processes, oxygen transport, pigmentation, and structural protein synthesis, including collagen and elastin. Recent research has elucidated its pivotal role in innate immunity of crustaceans, enhancing the immune response by promoting phagocytic activity, antimicrobial peptide production, and modulation of immune gene expression. Copper ions exhibit antimicrobial effects by disrupting cell membranes and inhibiting microbial proliferation. Furthermore, copper governs antioxidant defense mechanisms, protecting crustaceans against oxidative stress and infection. However, excessive copper can lead to toxicity, highlighting the need for strict maintenance of copper homeostasis. This review explores the complex processes of copper homeostasis in crustaceans, detailing transport mechanisms, storage proteins, and detoxification pathways. It emphasizes copper's critical physiological and immunological functions, contributing to a comprehensive understanding of its multifaceted roles in crustaceans and laying groundwork for further exploration of copper homeostasis as a strategy for boosting crustacean immunity. Aquaculture practices significantly influence copper levels in crustaceans. Effective copper management, including monitoring techniques, water treatment strategies, and regulatory frameworks, is crucial for both crustacean welfare and environmental sustainability.

Leveraging GIS-based AHP, remote sensing, and machine learning for susceptibility assessment of different flood types in peshawar, Pakistan - Muhammad Tayyab; Muhammad Hussain; Jiquan Zhang; Safi Ullah; Zhijun Tong; Zahid Ur Rahman; Ali R. Al-Aizari; Bazel Al-Shaibah (Journal of Environmental Management, 2024)

Role of exogenous silica fertilization and genotype selection in attenuating oxidative and osmotic stress in wheat (Triticum aestivum L.) under water deficit conditions - Muhammad Anwar ul Haq; Muhammad Nadeem; Munaza Naseem; Ghulam Hasan Abbasi; Muhammad Ali; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Tayyab Mehmood; Muhammad Awais; Rizwan Ullah; Tasawar Ali (Plant and Soil, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Synergistic biochar and Serratia marcescens tackle toxic metal contamination: A multifaceted machine learning approach - Hamid Rehman; Aqib Hassan Ali Khan; Tayyab Ashfaq Butt; Muhammad Toqeer; Muhammad Bilal; Mahtab Ahmad; Ahmed Abdullah Alawi Al-Naghi; Enamur Rahim Latifee; Omar Ali Saad Algassem; Mazhar Iqbal (Journal of Environmental Management, 2024)

Effects of enzymatic hydrolysis combined with glycation on the emulsification characteristics and emulsion stability of peanut protein isolate - Meiyue Wang; Guanhao Bu; Tingwei Zhu; Jia Liu; Mengyao Li; Muhammad Tayyab Rashid; Mengqing Han (Food Research International, 2024)

The mucosal immunity in crustaceans: Inferences from other species - Ruixue Hao; Mingming Zhao; Muhammad Tayyab; Zhongyang Lin; Yueling Zhang (Fish & Shellfish Immunology, 2024)

Navigating the environmental dynamics, toxicity to aquatic organisms and human associated risks of an emerging tire wear contaminant 6PPD-quinone - Syed Shabi Ul Hassan Kazmi; Qiao Xu; Muhammad Tayyab; Paolo Pastorino; Damià Barcelò; Zaher Mundher Yaseen; Zulqarnain Haider Khan; Gang Li (Environmental Pollution, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Microplastics in agroecosystems: Soil-plant dynamics and effective remediation approaches - Muhammad Tayyab; Syed Shabi Ul Hassan Kazmi; Paolo Pastorino; Hafiz Sohaib Ahmed Saqib; Zaher Mundher Yaseen; Muhammad Sajid Hanif; Waqar Islam (Chemosphere, 2024)

Microsatellite and mtDNA-based exploration of inter-generic hybridization and patterns of genetic diversity in major carps of Punjab, Pakistan - Shakeela Parveen; Khalid Abbas; Muhammad Tayyab; Muhammad Hussain; Huma Naz; Laiba Shafique (Aquaculture International, 2024)

Vertical variations and environmental heterogeneity drove the symphony of periphytic protozoan fauna in marine ecosystems - Syed Shabi Ul Hassan Kazmi; Muhammad Tayyab; Uroosa; Paolo Pastorino; Damià Barcelò; Sohrab Khan; Zaher Mundher Yaseen (Science of The Total Environment, 2024)

Decoding the molecular concerto: Toxicotranscriptomic evaluation of microplastic and nanoplastic impacts on aquatic organisms - Syed Shabi Ul Hassan Kazmi; Muhammad Tayyab; Paolo Pastorino; Damià Barcelò; Zaher Mundher Yaseen; Hans-Peter Grossart; Zulqarnain Haider Khan; Gang Li (Journal of Hazardous Materials, 2024)

Facile synthesis of novel zinc ferrite nanostructures (ZFN) for enhanced adsorption of highly mobile and toxic As(III) from aqueous solutions - Khurram Shehzad; Zhu Haifeng; Mukhtar Ahmad; Kareem Yusuf; Muhammad Tayyab Butt; Muniba Rahmat; Weihong Xu; Jinhuai Liu; Yuanguo Xu (Journal of Water Process Engineering, 2024)

Quantitative seismicity of shale gas reservoirs of the Lower and Middle Indus Basin (Pakistan) revealed from instantaneous spectral decomposition-based inverted Vp/Vs ratio simulation - Muhammad Tayyab Naseer (Journal of Asian Earth Sciences, 2024)

Comparative genomic studies on the TGF-β superfamily in blue whale - Zunaira Faiz; Shakeela Parveen; Saba Saeed; Muhammad Tayyab; Mehwish Sultana; Muhammad Hussain; Zainab Shafqat (Mammalian Genome, 2024)

Genetic characterization, structural analysis, and detection of positive selection in small heat shock proteins of Cypriniformes and Clupeiformes - Mehwish Sultana; Muhammad Tayyab; Shakeela Parveen; Muhammad Hussain; Laiba Shafique (Fish Physiology and Biochemistry, 2024)

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Seismic attributes and instantaneous spectral analysis-based temperature-porosity simulations: An example of imaging shale gas-bearing basin floor fans of early-Cretaceous delta sequences, Southeast Asian Basin - Muhammad Tayyab Naseer; Shazia Naseem; Ahmed E. Radwan; Aisha M. Alqahtani; Ilyas Khan; A. Singh (Journal of Asian Earth Sciences, 2024)

Energy security dimensions and economic growth in Non-OECD Asia: An analysis on the role of institutional quality with energy policy implications - Muhammad Tayyab Ayaz; Tina Prodromou; Thanh Le; Rabindra Nepal (Energy Policy, 2024)

Seismic attributes and quantitative reverse reservoir simulations of shallow-marine eocene sedimentary fairways, extensional rifting Indus onshore petroleum system, southern Pakistan: Implications for hydrocarbon exploration - Muhammad Tayyab Naseer (Marine and Petroleum Geology, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Development of Maghemite Nanoparticles to Effectively Adsorb Methylene Blue Dye from Water - Muhammad Azeem Ashraf; Mumtaz Hasan Malik; Assad Farooq; Muhammad Tayyab Noman; Nayab Khan (Water, Air, & Soil Pollution, 2024)

Water resource management and flood mitigation: hybrid decomposition EMD-ANN model study under climate change - Nisar Ahmad; Xu Yi; Muhammad Tayyab; Muhammad Hamza Zafar; Naureen Akhtar (Sustainable Water Resources Management, 2024)
The growing population and the rise in urbanization have made managing water a critical concern around the world in recent years. Globally, flooding is one of the most devastating natural disasters. Flood risk mitigation relies heavily on accurate and consistent streamflow forecasts. Pakistan Upper Indus Basin (UIB) is most vulnerable to flooding. Floods have become more frequent in recent decades. UIB can be divided into sub-regions due to its landscape variability, and its collective impact is most prominent in the Massam region. UIB hydrological and meteorological station observations have been used to study seasonal hydro-meteorological variations. To predict flooding, this study proposes a hybrid model combining artificial neural networks as multi-layer perceptron (MLPs) in feed-forward mode, along with empirical mode decomposition (EMD). Data collected by the surface-water hydrology project and Pakistan Meteorological Department from 1960 to 2012, 1969 to 2012, and 1972 to 2012 have been utilized from 17 locations. Statistical parameters and Nash–Sutcliffe Efficiency were measured to analyze the model’s prowess. As a result, decomposition-based models perform better than AI-based models when it comes to prediction accuracy. MLPQTP-EMD performed exceptionally better than competing AI models. The results are further validated by performing a peak value analysis during the flooding season (June–September) achieving a remarkable 91.3% score adding a 5.6% increase by EMD for input data achieving 39.3–32.3% statistical indices scores.

Spatiotemporal distribution and population trends of Sindh ibex (Capra aegagrus blythii) in Balochistan during 2019–2022 - Najeeb Ullah; Irum Basheer; Zhang Minghai; Muhammad Nawaz Rajpar; Muhammad Rehan; Muhammad Tayyab Khan (European Journal of Wildlife Research, 2024)
The increased pressures generated by human activities in form of climate change and habitat fragmentation have caused serious threats for Sindh ibex ( Capra aegagrus blythii ). Balochistan, recognized as one of the most vulnerable regions to climate change in Pakistan, has limited data on the distribution and population status of this species. To address this gap, our study aims to assess the spatial and temporal distribution and population trend of Sindh ibex in the Khuzdar and Lasbela districts of Balochistan. The study covered an area of approximately 45,123.97 km 2 . It involved a double-observer survey at ten sites from 2019 to 2022, using the BBRecapture package in the R programming language to estimate ibex population trend and dispersion. We provided a comprehensive update of the species geographic range, along with estimates of its current abundance and population trends. Over the course of four years, the ibex population fluctuated. The ibexes detected dropped from 720 (male to female ratio 1:1.21) and 710 (male to female ratio 1:1.08) in 2019 and 2020, respectively, to 550 (male to female ratio 1:1.35) and 548 (male to female ratio 1:1.09). Overall, this study provides valuable insights into the population trends, gender ratios, habitat preferences, and density of Sindh ibex in Balochistan over the four-year period. These findings contribute significantly to the baseline data on the species ecology and will further help in the conservation of these species at local scale.

Retraction Note: The shadow economy in South Asia: dynamic effects on clean energy consumption and environmental pollution - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman; Zubaria Andlib (Environmental Science and Pollution Research, 2024)

Harnessing probiotics and prebiotics as eco-friendly solution for cleaner shrimp aquaculture production: A state of the art scientific consensus - Muhammad Noman; Syed Shabi Ul Hassan Kazmi; Hafiz Sohaib Ahmed Saqib; Usama Fiaz; Paolo Pastorino; Damià Barcelò; Muhammad Tayyab; Wenhua Liu; Zhen Wang; Zaher Mundher Yaseen (Science of The Total Environment, 2024)

Seismic attributes and quantitative inverse dynamical simulations for characterization of late Cretaceous classical fluvial meander channelized stratigraphic traps system, onshore Indus, Pakistan: Implications for hydrocarbon exploration - Muhammad Tayyab Naseer (Marine and Petroleum Geology, 2024)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

Application of seismic attributes and quantitative-based instantaneous static reservoir simulations for quantitative imaging of lithology and fluids of Lower-Cretaceous hydrocarbon-bearing delta traps, Onshore, Pakistan - Muhammad Tayyab Naseer (Journal of Earth System Science, 2024)

Does environmental policy stringency reduce trade in energy resources? Insights from coal, petroleum, and gas - Ahmed Usman; Sana Ullah; Ilhan Ozturk; Sidra Sohail; Muhammad Tayyab Sohail (Resources Policy, 2024)

How do digital inclusion and energy security risks affect mineral resources trade? Evidence from world-leading mineral trading countries - Muhammad Tayyab Sohail; Norashidah Md Din (Resources Policy, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Seismic Attributes and Inverse Quantitative Static Density–Porosity–Constraint Reservoir Simulations of Naturally-Fractured Hydrocarbon-Bearing Lower Cretaceous Shallow-Marine Architectures, Onshore Indus, Pakistan - Muhammad Tayyab Naseer (Natural Resources Research, 2024)

Facile green synthesis of Phyllanthus emblica extract based Ag-NPs for antimicrobial and response surface methodology based catalytic reduction applications - Urooj Fatima; Hummera Rafique; Sadia Akram; Season Si Chen; Khalida Naseem; Jawayria Najeeb; Muhammad Tayyab (Journal of Cleaner Production, 2024)

How does formal credit promote green entrepreneurship? New insights from renewable energy producers in high-, middle-, and low-income countries - Muhammad Tayyab Sohail; Norashidah Md Din (Environmental Science and Pollution Research, 2023)

Synergistic effect of extracellular adenosine triphosphate and quercetin on post-thaw quality and fertilization potential of Lohi ram sperm - Muhammad Tayyab Khan; Muhammad Irfan-ur-Rehman Khan; Ejaz Ahmad; Muhammad Rizwan Yousaf; Muhammad Oneeb (Cryobiology, 2023)

Green development in BRICS: unraveling the effects of environmental technology, R&D spending, and green investment in the context of COP21 - Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

Rural areas development and pro-environmental behavior in China: implications for rural development and planning - Xiaoli Cao; Yingxia Yun; Lijian Ren; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

Transcriptomic analysis of Ralstonia solanacearum in response to antibacterial volatiles of Bacillus velezensis FZB42 - Hafiz Abdul Samad Tahir; Qurban Ali; Faheem Uddin Rajer; Qaisar Shakeel; Waqqas Gillani; Rana Binyamin; Hafiz Muhammad Abdullah Tayyab; Abdur Rashid Khan; Qin Gu; Xuewen Gao; Huijun Wu (Archives of Microbiology, 2023)

DNA metabarcoding reveals evidence of inter- and intra-guild predation by Scylla paramamosain in a marine ecosystem - Hafiz Sohaib Ahmed Saqib; Ye Yuan; Syed Shabi Ul Hassan Kazmi; Muhammad Tayyab; Zifei Xiang; Mhd Ikhwanuddin; Hongyu Ma (Frontiers in Marine Science, 2023)
Introduction Crustacean predators exhibit diverse trophic interactions across various habitats in aquatic ecosystems. To assess their ecological roles, it is essential to understand their complete dietary spectrum. Recently, DNA-based techniques such as DNA metabarcoding and high-throughput sequencing have provided insights into trophic networks and their response to environmental drivers. Methods In this study, we used these methods to investigate the impact of salinity gradients on the trophic networks of mud crabs (Scylla paramamosain) in marine ecosystems. Results Our results revealed that mud crabs prey on a wide range of taxa, including crabs (other than the host species), fish, shrimps, and other prey factions. Salinity gradients had a significant influence on the specific prey items, such as high predation on Metapenaeus, and Trigonopterus species in high salinity sites. Notably, crabs exhibited a greater infestation of Portunion parasites in environments with high salinity levels, in contrast to environments with lower salinity levels. Ordination analysis showed that mud crabs adapt their diet according to environmental constraints. Discussion Furthermore, the results indicate that mud crabs showed opportunistic predation behavior as they were observed preying on other Portunidae species sharing the same trophic guild. Overall, these findings demonstrate the dietary plasticity and associated parasite infestation of an important crustacean predator, and provide evidence that environmental changes may affect incidences of the associated parasites as well as the specific predator-prey interactions indirectly through fluctuations in marine ecosystems.

Application of continuous porosity-dependent decomposed density and velocity geophysical modelling for 4-D Seismic-based Quantification of hydrocarbon-bearing upper-Cretaceous stratigraphic systems, Southern Onshore, Pakistan - Muhammad Tayyab Naseer; Shazia Naseem (Journal of Applied Geophysics, 2023)

Multiplex Cas9-based excision of CLCuV betasatellite and DNA-A revealed reduction of viral load with asymptomatic cotton plants - Sana Shakoor; Abdul Qayyum Rao; Sara Ajmal; Aneela Yasmeen; Muhammad Azmat Ullah Khan; Sahar Sadaqat; Naeem Mahmood Ashraf; Felix Wolter; Michael Pacher; Tayyab Husnain (Planta, 2023)

Sustainable development through corporate social responsibility adoption and its drivers: evidence from corporate industrial sector - Hussain Bux; Zhe Zhang; Muhammad Tayyab Sohail; Naveed Ahmad; Adnan Ali (Environmental Science and Pollution Research, 2023)

Identification, characterization and expression profiling of salt-stress responsive proteinase inhibitor in Gossypium arboreum L. - Muhammad Naveed Shahid; Sarfraz Kiani; Bushra Rashid; Tayyab Husnain (South African Journal of Botany, 2023)

Evaluating policy-driven capital for renewable energy investments in the presence of cross-sectional dependence: perspectives from financial institutions and markets - Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

The perception and influencing factors of astringency, and health-promoting effects associated with phytochemicals: A comprehensive review - Fang Wei; Jie Wang; Liyong Luo; Muhammad Tayyab Rashid; Liang Zeng (Food Research International, 2023)

Development of a new integrated flood resilience model using machine learning with GIS-based multi-criteria decision analysis - Muhammad Hussain; Muhammad Tayyab; Kashif Ullah; Safi Ullah; Zahid Ur Rahman; Jiquan Zhang; Bazel Al-Shaibah (Urban Climate, 2023)

Integrating by-products from bioenergy technology to improve the morpho-physiological growth and yield of soybean under acidic soil - Muhammad Tayyab Sattar; Ali Raza; Shafaqat Ali; Shanzay Bashir; Farah Kanwal; Imran Khan; Muhammad Ali Raza; Sajad Hussain; Fei Shen (Chemosphere, 2023)

Spectral Decomposition-Based Quantitative Inverted Velocity Dynamical Simulations of Early Cretaceous Shaly-Sandstone Natural Gas System, Indus Basin, Pakistan: Implications for Low-Velocity Anomalous Zones for Gas Exploration - Muhammad Tayyab Naseer (Natural Resources Research, 2023)

Appraisal of tectonically-influenced lowstand prograding clinoform sedimentary fairways of Early-Cretaceous Sember deltaic sequences, Pakistan using dynamical reservoir simulations: Implications for natural gas exploration - Muhammad Tayyab Naseer (Marine and Petroleum Geology, 2023)

Country risk and its impact on renewable energy investment in highly polluted economies - Huang Ren; Xu Qifeng; Guan Yongjun; Xu Yunbao; Hu Gaole; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2023)

Imaging Lowstand prograding stratigraphic pinch-out traps of a Lower Cretaceous clastic system using inverted seismic-based porosity simulation of SE-Asian Basin: Implications for petroleum exploration - Muhammad Tayyab Naseer; Shazia Naseem; Dyana Aziz Bayz (Marine and Petroleum Geology, 2023)

Enhancing photothermal VOCs removal in ZnO-based catalysts via transition metal-based band edge tuning and oxygen vacancy engineering - Bernard Jomari Razote; Muhammad Tayyab; Daiha Shin; Kyung-Min Kim; Chang-Ha Lee (Journal of Environmental Chemical Engineering, 2023)

Seismic stratigraphy and attributes application for imaging a Lower Cretaceous deltaic system: Sukkur rift zone, Lower Indus Basin, Pakistan - Perveiz Khalid; Asam Farid; Muhammad Tayyab Naseer; Qamar Yasin; Shazia Naseem (Marine and Petroleum Geology, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

Centella asiatica (L.) Urb. Extract ameliorates branched-chain amino acid (BCAA) metabolism in acute reserpine-induced stress zebrafish model via 1H Nuclear Magnetic Resonance (NMR)-based metabolomics approach - Fauziahanim Zakaria; Muhammad Tayyab Akhtar; Wan Ibrahim Wan Norhamidah; Abu Bakar Noraini; Azira Muhamad; Shamarina Shohaimi; Maulidiani; Hafandi Ahmad; Intan Safinar Ismail; Nor Hadiani Ismail; Khozirah Shaari (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Application of instantaneous spectral decomposition-based porosity simulations for imaging shallow-marine stratigraphic traps of Lower-Eocene carbonates sequences of Indus Basin, Onshore Pakistan - Muhammad Tayyab Naseer (Journal of Earth System Science, 2023)

Reflection seismic-based imaging of meandering channels of Lower Indus Plain using wavelet transform-based density-porosity hydro-geophysical simulations: Implications on water exploration - Muhammad Tayyab Naseer; Shazia Naseem; Rebwar Nasir Dara (Journal of Applied Geophysics, 2023)

3-D quantitative seismic imaging of tectonically-influenced Middle-Eocene carbonates stratigraphic traps of SE-Asian basins using spectral decomposition: Implications for hydrocarbon exploration - Muhammad Tayyab Naseer; Shazia Naseem; Dyana Aziz Bayz (Journal of Applied Geophysics, 2023)

A new breakthrough in photocatalytic hydrogen evolution by amorphous and chalcogenide enriched cocatalysts - Muhammad Tayyab; Yujie Liu; Zhiguo Liu; Zehong Xu; Wenhui Yue; Liang Zhou; Juying Lei; Jinlong Zhang (Chemical Engineering Journal, 2023)

Examining the potential role of ICT diffusion on green growth: does financial development matter in BRICS economies? - Yuping Tang; Wanling Chen; Shaoming Chen; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

A PLS-SEM approach to determine farmers’ awareness about climate change mitigation and adaptation strategies: pathway toward sustainable environment and agricultural productivity - Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Does education matter in China? Myths about financial inclusion and energy consumption - Yukun Li; Jian Chen; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Determinants of China’s renewable energy industry development: do eco-innovation and financial inclusion matter? - Peng Liu; Xinwei Gao; Lei Yu; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Correction to: Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Impact of spatial and temporal changes in climate on the Kunhar River Watershed, Pakistan - Ghulam Nabi; Muhammad Tayyab; Haseeb Akbar; Muhammad Arfan; Ijaz Ahmad; Muhammad Masood; Aqeela Zahra (Arabian Journal of Geosciences, 2022)

Asymmetric determinants of CO2 emissions in China: do government size and economic size matter? - Hai Lan; Chengping Cheng; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Environmental costs of political instability in Pakistan: policy options for clean energy consumption and environment - Muhammad Tayyab Sohail; Muhammad Tariq Majeed; Parvez Ahmed Shaikh; Zubaria Andlib (Environmental Science and Pollution Research, 2022)

Sugarcane cultivar-dependent changes in assemblage of soil rhizosphere fungal communities in subtropical ecosystem - Muhammad Tayyab; Nyumah Fallah; Caifang Zhang; Ziqin Pang; Waqar Islam; Sheng Lin; Wenxiong Lin; Hua Zhang (Environmental Science and Pollution Research, 2022)

Does financial inclusion and education limit CO2 emissions in China? A new perspective - Nan Liu; Cencen Hong; Muhammad Tayyab Sohail (Environmental Science and Pollution Research, 2022)

Environmental benefit of clean energy consumption: can BRICS economies achieve environmental sustainability through human capital? - Yanyan Liu; Muhammad Tayyab Sohail; Arman Khan; Muhammad Tariq Majeed (Environmental Science and Pollution Research, 2022)

Imaging of Stratigraphic Pinch-Out Traps Within the Lower-Cretaceous Shaly-Sandstone System, Pakistan, Using 3D Quantitative Seismic Inverted Porosity–Velocity Modeling - Muhammad Tayyab Naseer (Natural Resources Research, 2021)

Examining the role of non-economic factors in energy consumption and CO2 emissions in China: policy options for the green economy - Lin Jian; Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed (Environmental Science and Pollution Research, 2021)

Management of green economy in China and India: dynamics of poverty and policy drivers - Anyin Jiang; Ying Cao; Muhammad Tayyab Sohail; Muhammad Tariq Majeed; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Sugarcane monoculture drives microbial community composition, activity and abundance of agricultural-related microorganisms - Muhammad Tayyab; Ziqi Yang; Caifang Zhang; Waqar Islam; Wenxiong Lin; Hua Zhang (Environmental Science and Pollution Research, 2021)

Heat shock protein gene identified from Agave sisalana (AsHSP70) confers heat stress tolerance in transgenic cotton (Gossypium hirsutum) - Anicet Agossa Batcho; Muhammad Bilal Sarwar; Bushra Rashid; Sameera Hassan; Tayyab Husnain (Theoretical and Experimental Plant Physiology, 2021)

Renewable energy and non-renewable energy consumption: assessing the asymmetric role of monetary policy uncertainty in energy consumption - Muhammad Tayyab Sohail; Yu Xiuyuan; Ahmed Usman; Muhammad Tariq Majeed; Sana Ullah (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: The shadow economy in South Asia: dynamic effects on clean energy consumption and environmental pollution - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman; Zubaria Andlib (Environmental Science and Pollution Research, 2021)
This study explores the symmetric and asymmetric effects of the shadow economy on clean energy and air pollution of South Asian countries over the period 1991–2019. The short-run ARDL findings for the clean energy model suggest that shadow economy increases clean energy consumption in Pakistan and Sri Lanka, whereas this effect is negative for India and insignificant for other countries. The long-run results indicate the adverse impact only for India and the effects of tax revenue on clean energy are positively significant in Sri Lanka while negatively signiicant in Nepal and Bangladesh. Institutional quality significantly increases clean energy in Pakistan, India, and Nepal. However, in the case of Pakistan and Nepal, institutional quality deteriorated the environmental quality. The results for the pollution model confer that shadow economy increases emissions in Pakistan, decreases in Bangladesh and Nepal, and has no effect in India and Sri Lanka. The nonlinear ARDL results reveal that the positive components of the shadow economy significantly increase clean energy consumption only in Pakistan; however, the negative components of the shadow economy are negatively significant in all countries except Sri Lanka and Nepal. However, the negative component of the informal sector of the economy reduces CO2 emissions in India and increases CO2 emissions in Bangladesh and Nepal. The results offer important policy implications for achieving clean energy and better environmental quality in South Asian countries.

Pakistan management of green transportation and environmental pollution: a nonlinear ARDL analysis - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman (Environmental Science and Pollution Research, 2021)
Modern advances in nonlinear modeling have exposed that nonlinear models yield more robust results compared with linear models. Research on the effect of air-railway transportation on environmental pollution has now arrived into a new way of asymmetry analysis and captured the real issue among the nexus. This study aims to inspect the asymmetric impact of air-railway transportation on environmental pollution in Pakistan by using annual time series data from 1991 to 2019. The findings show that positive shock in air passenger carried and railway passenger carried increases carbon emissions, which implies that 1% increase in air passenger carried (railway passenger carried) enhances environmental pollution by 0.21% (0.32%) in long run in Pakistan. While positive shock in railway passengers carried increases environmental pollution and negative shock in railway passengers carried decreases the environmental pollution in the short run. The outcomes have also confirmed the short- and long-run asymmetries in Wald statistics. The findings are country-specific and it would be regionally specific.

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Current findings on carp edema virus, control challenges, and future outlook - Tayyab Rehman; Lizi Yin; Muhammad Bilal Latif; Yaojia Zhou; Kaiyu Wang; Yi Geng; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Hongrui Guo; Weiming Lai; et al. (Aquaculture International, 2020)

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Transcriptomic analysis of root specific drought mediated response of G. arboreum and G. hirsutum - Zarnab Ahmad; Sajjad Sadique; Muhammad B. Sarwar; Bushra Rashid; Sameera Hassan; Sultana Rasheed; Khurram Bashir; Motoaki Seki; Tayyab Husnain (Biologia, 2020)

Identification and validation of superior housekeeping gene(s) for qRT-PCR data normalization in Agave sisalana (a CAM-plant) under abiotic stresses - Muhammad Bilal Sarwar; Zarnab Ahmad; Batcho Agossa Anicet; Moon Sajid; Bushra Rashid; Sameera Hassan; Mukhtar Ahmed; Tayyab Husnain (Physiology and Molecular Biology of Plants, 2020)

Effective plant-endophyte interplay can improve the cadmium hyperaccumulation in Brachiaria mutica - Muhammad Tayyab Ahsan; Razia Tahseen; Abida Ashraf; Abid Mahmood; Muhammad Najam-ul-haq; Muhammad Arslan; Muhammad Afzal (World Journal of Microbiology and Biotechnology, 2019)

Investigating the drinking and surface water quality and associated health risks in a semi-arid multi-industrial metropolis (Faisalabad), Pakistan - Yusra Mahfooz; Abdullah Yasar; Muhammad Tayyab Sohail; Amtul Bari Tabinda; Rizwan Rasheed; Samina Irshad; Balal Yousaf (Environmental Science and Pollution Research, 2019)

Rainfall-runoff modeling at Jinsha River basin by integrated neural network with discrete wavelet transform - Muhammad Tayyab; Jianzhong Zhou; Xiaohua Dong; Ijaz Ahmad; Na Sun (Meteorology and Atmospheric Physics, 2019)

Synthesis and applications of nano-TiO2: a review - Muhammad Tayyab Noman; Muhammad Azeem Ashraf; Azam Ali (Environmental Science and Pollution Research, 2019)

WRF model for precipitation simulation and its application in real-time flood forecasting in the Jinshajiang River Basin, China - Jianzhong Zhou; Hairong Zhang; Jianyun Zhang; Xiaofan Zeng; Lei Ye; Yi Liu; Muhammad Tayyab; Yufan Chen (Meteorology and Atmospheric Physics, 2018)

Application of instantaneous spectral analysis and acoustic impedance wedge modeling for imaging the thin beds and fluids of fluvial sand systems of Indus Basin, Pakistan - Muhammad Tayyab Naseer; Shazia Asim (Journal of Earth System Science, 2018)

Sucrose synthase genes: a way forward for cotton fiber improvement - Mukhtar Ahmed; Ahmad Ali Shahid; Sidra Akhtar; Ayesha Latif; Salah ud Din; Ma Fanglu; Abdul Qayyum Rao; Muhammad Bilal Sarwar; Tayyab Husnain; Wang Xuede (Biologia, 2018)

Development and validation of a loop-mediated isothermal amplification assay for the detection of Mycoplasma bovis in mastitic milk - Aqeela Ashraf; Muhammad Imran; Tahir Yaqub; Muhammad Tayyab; Wasim Shehzad; Claro N. Mingala; Yung-Fu Chang (Folia Microbiologica, 2018)

Porosity prediction of lower cretaceous unconventional resource play, south Indus Basin, Pakistan, using the seismic spectral decomposition technique - Muhammad Tayyab Naseer; Shazia Asim (Arabian Journal of Geosciences, 2018)

Modulation of Wnt signaling pathway by hepatitis B virus - Muhammad Daud; Muhammad Adeel Rana; Tayyab Husnain; Bushra Ijaz (Archives of Virology, 2017)

Application of spectral decomposition for the detection of fluvial sand reservoirs, Indus Basin, SW Pakistan - Muhammad N. Tayyab; Shazia Asim (Geosciences Journal, 2017)

Continuous wavelet transforms of spectral decomposition analyses for fluvial reservoir characterization of Miano Gas Field, Indus Platform, Pakistan - Muhammad Tayyab Naseer; Shazia Asim (Arabian Journal of Geosciences, 2017)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Impact of Distribution Type in Bayes Probability Flood Forecasting - Wei Li; Jianzhong Zhou; Huaiwei Sun; Kuaile Feng; Hairong Zhang; Muhammad Tayyab (Water Resources Management, 2017)

Spectral decomposition application for analyzing the structure and the reservoir potential: a case study of Penobscot, Nova Scotia offshore, Canada - Shazia Asim; Salman Ahmad; Peimin Zhu; Muhammad Tayyab Naseer; Mehwish Butt (Arabian Journal of Geosciences, 2016)

Escherichia coli expression of NDV fusion protein gene and determination of its antigenic epitopes - Naila Shahid; Sana Tahir; Abdul Q. Rao; Sameera Hassan; Anwar Khan; Ayesha Latif; Muhammad Au Khan; Bushra Tabassum; Ahmed A. Shahid; Ahmed U. Zafar; Tayyab Husnain (Biologia, 2015)

A case study of Precambrian to Eocene sediments’ hydrocarbon potential assessment in Central Indus Basin of Pakistan - Shazia Asim; Peimin Zhu; Shahid Nadeem Qureshi; Muhammad Tayyab Naseer (Arabian Journal of Geosciences, 2015)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Expression line approach to recombinant human epidermal growth factor into the yeast, Pichia pastoris from Huh-7 cell line - Mohsin Ahmad Khan; Faidad Khan; Nadeem Ahmad; Muhammad Islam Khan; Ahmad Usman Zafar; Tayyab Husnain (Molecular Biology Reports, 2014)

Identification of biotic and abiotic stress up-regulated ESTs in Gossypium arboreum - Muhammad Younas Khan Barozai; Tayyab Husnain (Molecular Biology Reports, 2012)

Antihaemorrhagic potentials of Fagonia cretica against Naja naja karachiensis (black Pakistan cobra) venom - Muhammad Tahir Razi; Muhammad Hassham Hassan Bin Asad; Taous Khan; Muhammad Zabta Chaudhary; Muhammad Tayyab Ansari; Muhammad Anwar Arshad; Qazi Najam-us Saqib (Natural Product Research, 2011)

Overexpression of the phytochrome B gene from Arabidopsis thaliana increases plant growth and yield of cotton (Gossypium hirsutum) - Abdul Qayyum Rao; Muhammad Irfan; Zafar Saleem; Idrees Ahmad Nasir; Sheikh Riazuddin; Tayyab Husnain (Journal of Zhejiang University-SCIENCE B, 2011)

Functional analysis of cotton small heat shock protein promoter region in response to abiotic stresses in tobacco using Agrobacterium-mediated transient assay - Muzna Zahur; Asma Maqbool; Muhammad Irfan; Muhammad Younas Khan Barozai; Uzma Qaiser; Bushra Rashid; Tayyab Husnain; Shiekh Riazuddin (Molecular Biology Reports, 2009)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)